(untitled) (REVISTA DIREITOS, TRABALHO E POLÍTICA SOCIAL, 2025)
This article examines a social group that is subjected to a multiplicity of forms of oppression: the Quilombolas of Brazil. Because of social isolation during the COVID-19 pandemic, which impeded their economic survival, they agitated for access to vaccines, thereby helping to bring healthcare to their communities. The documentary “We, Quilombola Women” [Eu, nós, elas, Quilombolas], and YouTube lives were analyzed using Content Analysis. Women’s empowerment through digital technology has been instrumental in advocating for the fundamental rights of these communities, thereby exerting pressure on the state to respond to the health crisis. The creation of new virtual networks of resilience and the opening of avenues for collective empowerment demonstrated that, even during a pandemic crisis, community participation could enhance the efficacy of public health policies with a focus on communicable disease prevention.